2012
DOI: 10.1673/031.012.11101
|View full text |Cite
|
Sign up to set email alerts
|

Global Collembola on Deception Island

Abstract: Three new non-indigenous springtail species are recorded in recent collections made on Deception Island, South Shetland Islands, maritime Antarctic: Deuteraphorura (Deuteraphorura) cebennaria (Gisin) (Collembola: Onychiuridae), Mesaphorura macrochaeta Rusek (Tullbergiidae), and Proisotoma minuta Axelson (Isotomidae). One of these, D. (D.) cebennaria, is described. Additionally, two new indigenous species, Mesaphorura macrochaeta Rusek and Proisotoma minuta Axelson, are also recorded. The total number of Collem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…It should be emphasized that the terrestrial invertebrate species mentioned in Table are ‘representative’—at present explicit evidence does not exist to enable differentiation across a wide diversity of representatives of these groups occurring naturally or already introduced in the wider sub‐Antarctic (especially South Georgia). However, Greenslade et al (), considering recent establishment of non‐native Collembola on Deception Island, noted that several of the species now present are identified as high risk in the assessment that Greenslade and Convey () applied to the sub‐Antarctic islands, again, highlighting the heightened risk associated with parts of the APR. Similarly, Russell et al () have reported several non‐native mite and springtail species recently established in the South Shetland Islands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be emphasized that the terrestrial invertebrate species mentioned in Table are ‘representative’—at present explicit evidence does not exist to enable differentiation across a wide diversity of representatives of these groups occurring naturally or already introduced in the wider sub‐Antarctic (especially South Georgia). However, Greenslade et al (), considering recent establishment of non‐native Collembola on Deception Island, noted that several of the species now present are identified as high risk in the assessment that Greenslade and Convey () applied to the sub‐Antarctic islands, again, highlighting the heightened risk associated with parts of the APR. Similarly, Russell et al () have reported several non‐native mite and springtail species recently established in the South Shetland Islands.…”
Section: Discussionmentioning
confidence: 99%
“…see Downie, Convey, McInnes, & Pugh, ; Russell et al, ). In particular, high human visitation of small geothermal areas on Deception Island can create literal ‘hot spots’ for non‐native species establishment, and the island contains the highest number of known non‐native species in Antarctica (Chown et al, ; Enríquez et al, ; Greenslade, Potapov, Russell, & Convey, ; Hughes, Pertierra, et al, ; Longton, ; Pertierra, Francisco, Benayas, Smith, & Hughes, ; Skottsberg, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayres et al (2008) observed reductions of up to 52 and 76%, respectively, in densities of two species of nematode, Scottnema lindsayae and Eudorylaimus sp., between paths with heavy pedestrian traffic and nearby undisturbed reference areas. Tejedo et al (2009) detected a clear decrease in Collembola abundance with increased pedestrian traffic, and Greenslade et al (2012) similarly noted large reductions in soil collembolan densities in areas on Deception Island subject to a high level of visitation relative to neighbouring undisturbed areas. Finally, some authors have proposed the possibility of non-indigenous species establishment as a direct result of the foot traffic associated with human presence, although there is still little evidence about the relative importance of this mechanism (Frenot et al 2005).…”
Section: Introductionmentioning
confidence: 88%
“…An additional three species of Cryptopygus are known from the Antarctic Peninsula and Scotia Arc Islands: Cryptopygus antarcticus antarcticus Willem, 1901 (type locality Gerlache Straits); Cryptopygus caecus (Wahlgren, 1906) (type locality South Georgia); and Cryptopygus badasa Greenslade, 1995 (type locality Livingston Island, Shetland Islands) (Greenslade 2010;Greenslade et al 2012). These species have wider distributions and are also found on subantarctic and maritime Antarctic islands.…”
Section: Introductionmentioning
confidence: 99%